Single cell meta-analysis of EndMT and EMT state in COVID-19 - Zhang, Lanlan; Tang, Chuang; Zhang, Min; Tong, Xia; Xie, Yingying; Yan, Ruitong; Wang, Xiangjun; Zhang, Xin; Liu, Dan; Li, Shasha (Frontiers in Immunology, 2022)
The prognosis of COVID-19 suggests that a proportion of patients develop fibrosis, but no evidence has been seen to indicate whether patients have progression of mesenchymal transition (MT) in the lungs. The role of MT during COVID-19 panic remain poorly understood. To describe the potential relationship between MT and SARS-COV-2 infection-induced pulmonary fibrosis. Using single-cell RNA sequencing, we profiled the transcriptomes of cells from the healthy(n=45), COVID-19 patients(n=58) and IPF(n=64) human lung to map the entire MT changing. This analysis enabled us to map all matrix-producing cells at high resolution and identify distinct subpopulations of endothelial cells (ECs) and epithelial cells as the primary cellular sources of MT clusters during COVID-19. For the first time, we identified early and late subgroups of endothelial mesenchymal transition (EndMT) and epithelial-mesenchymal transition (EMT) using analysis of public databases for single-cell sequencing. We assessed epithelial subgroups by age, smoking status, and gender, suggesting that the proportional changes in EMT in COVID-19 were statistically significant. Further enumeration of early and late EMT suggests a correlation between invasive genes and COVID-19. EndMT is upregulated in COVID-19 patients and enriched for more inflammatory cytokines. Further classifying EndMT as early or late stages, we found that just early EndMT was positively correlated with entry factors, however late EndMT was not correlated with fibroblasts. By exploring the statute of MT in COVID-19 patients, we hoped to mitigate the fibrosis impact of SARS-CoV-2 infection by offering plausible evidence.